Experimental study on enhanced heat transfer characteristics and flow instability of manifold microchannel - Ping Liu; Zhiwen Wang; Wenlong Zheng; Shiming Sang; Lianghong Hu; Ruiqi Sun; Yi Jin (Case Studies in Thermal Engineering)
This study investigates the enhanced heat transfer performance and flow instability in three types of manifold microchannels heat sinks: parallel manifold microchannel (PMMC), interrupted manifold microchannel (IMMC), and oblique break manifold microchannel (OMMC). The microchannels are fabricated on oxygen-free copper substrates using electrical discharge machining (EDM). The experiments utilize deionized water at varied mass flux (1389 kg m−2 s−1 to 5556 kg·m− 2·s−1) and inlet temperatures (20 °C and 50 °C), and the effects of heat flux on flow boiling characteristics, pressure drop, and thermal performance are analyzed. Results demonstrate that OMMC has the best overall heat transfer performance, particularly under high heat flux conditions, with a lower wall temperature compared to PMMC and IMMC. However, IMMC exhibits superior thermal uniformity, making it ideal for applications requiring stable temperature distribution. Moreover, as the mass flux increases, the pressure drop fluctuations of IMMC and OMMC show a nonlinear variation, which needs to be combined with the structural design to optimize the system stability. These findings provide critical insights for optimizing microchannel heat sink designs in high-performance cooling applications.